Calistung learning effectiveness using Zoom Cloud Meeting video for students in elementary school during Covid-19 pandemic - Adelia Eka Putri Nuraini; Asri Wibawa Sakti (Universitas Pendidikan Indonesia, 2021)
During the Covid-19 pandemic, learning loss is vulnerable to occur in early grade students, as well as what happens to learning basic skills in Calistung. This study aims to determine the effectiveness of e-learning during the Covid-19 pandemic in Indonesia using Zoom Cloud Video Meeting. The approach that we used in this study is quantitative, which is the type of research designed with a pretest-posttest control group. The results showed that the average effectiveness of the students in elementary school was categorized as still effective despite changes in learning time and the use of learning media. Students' understanding of the material for the Calistung learning can be improved by providing material via games or YouTube, which is done online by using the Zoom Cloud Meeting Video application with educators. The results of the research show that the average posttest score of students is 77.77%, greater than the average pretest score of 67.93%, so the difference is 9.84%. Therefore, Zoom Cloud Video Meeting can increase students' achievement in Calistung learning.